Galanin (1-15) enhances the effects of Fluoxetine in an animal model of depression. Role of the 5-HT1A receptor. - Pineda-Gómez, Juan Pedro; Flores-Burgess, Antonio; Millón-Peñuela, Carmelo; Cantero-García, Noelia; Flores Gómez, Marta; Puigcerver-Martínez, Araceli; Díaz-Cabiale, Zaida (My University, 2023)
Major depression is one of the most significant contributors to global disability. Selective serotoninergicreuptake inhibitors, including Fluoxetine (FLX), are the most commonly used antidepressant but are onlyeffective in 50% of patients. In recent studies, we observed that the N-terminal fragment of Galanin [GAL(1-15)]enhanced the antidepressant effects of FLX in naïve rodents. In this study, we analyzed the effect of GAL(1-15) in combination with FLX in an animal model of depression,the olfactory bulbectomy (OBX) rat, in the forced swimming test (FST) and the sucrose preference test (SPT)tests, related with despair and anhedonic behaviors. We also studied the role of the hippocampal 5-HT1AR inGAL(1-15)-enhancing effects using quantitative autoradiographic techniques. Groups of rats (n=7-9) received a subchronic pattern of FLX(10mg/Kg) alone or in combination with GAL(1-15)(1nmol) 15 min before the tests. Then, brains were removed, and coronal sections were obtained at the dorsalhippocampus. Saturation experiments were performed using [3H]-8-OH-DPAT. One-way ANOVA followed byFisher ́ s least significant difference test was used. Our results show that GAL(1-15)+FLX induced a decrease in the immobility time (p<0.05) and an increase inswimming by 30% (p<0.01) compared with FLX in the FST. In the SPT, only the combination of GAL(1-15)+FLXcould reverse the anhedonic behavior of OBX rats, increasing the sucrose intake (p<0.05) and preference(p<0.05). The combination of GAL(1-15)+FLX decreases the Kd and increases the Bmax value of 5-HT1A (p<0,05) in DGcompared with FLX in OBX animals. In conclusion, combining GAL(1-15)+FLX suggests a new augmentation strategy for treating depression.
Keywords: Neuropéptidos; Antidepresivos; Galanin(1-15); Depression; Fluoxetine